EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen